Phage Cocktails with Daptomycin and Ampicillin Eradicates Biofilm-Embedded Multidrug-Resistant Enterococcus faecium with Preserved Phage Susceptibility - Ashlan J. Kunz Coyne; Kyle Stamper; Razieh Kebriaei; Dana J. Holger; Amer El Ghali; Taylor Morrisette; Biswajit Biswas; Melanie Wilson; Michael V. Deschenes; Gregory S. Canfield; Breck A. Duerkop; Cesar A. Arias; et al. (Antibiotics, 2022)
Multidrug-resistant (MDR) Enterococcus faecium is a challenging nosocomial pathogen known to colonize medical device surfaces and form biofilms. Bacterio (phages) may constitute an emerging anti-infective option for refractory, biofilm-mediated infections. This study evaluates eight MDR E. faecium strains for biofilm production and phage susceptibility against nine phages. Two E. faecium strains isolated from patients with bacteremia and identified to be biofilm producers, R497 (daptomycin (DAP)-resistant) and HOU503 (DAP-susceptible dose-dependent (SDD), in addition to four phages with the broadest host ranges (ATCC 113, NV-497, NV-503-01, NV-503-02) were selected for further experiments. Preliminary phage-antibiotic screening was performed with modified checkerboard minimum biofilm inhibitory concentration (MBIC) assays to efficiently screen for bacterial killing and phage-antibiotic synergy (PAS). Data were compared by one-way ANOVA and Tukey (HSD) tests. Time kill analyses (TKA) were performed against R497 and HOU503 with DAP at 0.5× MBIC, ampicillin (AMP) at free peak = 72 µg/mL, and phage at a multiplicity of infection (MOI) of 0.01. In 24 h TKA against R497, phage-antibiotic combinations (PAC) with DAP, AMP, or DAP + AMP combined with 3- or 4-phage cocktails demonstrated significant killing compared to the most effective double combination (ANOVA range of mean differences 2.998 to 3.102 log10 colony forming units (CFU)/mL; p = 0.011, 2.548 to 2.868 log10 colony forming units (CFU)/mL; p = 0.023, and 2.006 to 2.329 log10 colony forming units (CFU)/mL; p = 0.039, respectively), with preserved phage susceptibility identified in regimens with 3-phage cocktails containing NV-497 and the 4-phage cocktail. Against HOU503, AMP combined with any 3- or 4-phage cocktail and DAP + AMP combined with the 3-phage cocktail ATCC 113 + NV-497 + NV-503-01 demonstrated significant PAS and bactericidal activity (ANOVA range of mean differences 2.251 to 2.466 log10 colony forming units (CFU)/mL; p = 0.044 and 2.119 to 2.350 log10 colony forming units (CFU)/mL; p = 0.028, respectively), however, only PAC with DAP + AMP maintained phage susceptibility at the end of 24 h TKA. R497 and HOU503 exposure to DAP, AMP, or DAP + AMP in the presence of single phage or phage cocktail resulted in antibiotic resistance stabilization (i.e., no antibiotic MBIC elevation compared to baseline) without identified antibiotic MBIC reversion (i.e., lowering of antibiotic MBIC compared to baseline in DAP-resistant and DAP-SDD isolates) at the end of 24 h TKA. In conclusion, against DAP-resistant R497 and DAP-SDD HOU503 E. faecium clinical blood isolates, the use of DAP + AMP combined with 3- and 4-phage cocktails effectively eradicated biofilm-embedded MDR E. faecium without altering antibiotic MBIC or phage susceptibility compared to baseline.